Technology-enhanced formative assessment in higher education: A voice from Indonesian EFL teachers - Roghibatul Luthfiyyah; Aisyah Aisyah; Gunadi Harry Sulistyo (EduLite: Journal of English Education, Literature and Culture, 2021)
The integration of information communication and technology in language teaching has been intensely examined in literature works. However, the study which explicitly investigates the advancement of technology for language assessment in higher education level is still underexplored, particularly in a formative assessment area. To fill that gap, the present study aims at investigating the perceptions of EFL teachers towards technology-enhanced formative assessment and how they implement it in the classroom. This study employs a qualitative case study approach. Of three participants from different universities were voluntarily participated in a semi-structured interview. The interview seeks to investigate the perceptions of teachers towards technology-enhanced assessment, the roles of technology in formative assessment, and the impact of technology on language learning. The findings reveal that EFL teachers view formative assessment as well as technology in a positive perception. They admit that technology is a practical tool that has multiple roles and it is deemed as useful and meaningful platform for assessing students. Finally, technology-enhanced formative assessment gives an impact on students’ performance, particularly on language accuracy. The further implications are discussed in this paper.